Canada Geese of the Mississippi Flyway with Special Reference to an Illinois Flock - Hanson, Harold Carsten; Smith, Robert H. (Champaign : Illinois Natural History Survey, 1950)
This Canada goose study is based on data from three primary sources : data collected at Horseshoe Lake, Alexander County, Illinois surveys by the authors on the distribution, habitat, and behavior of the population elsewhere in the Mississippi flyway and banding records of the Jack Miner Bird Sanctuary, Kingsville, Ontario. Data from other sources have been used as indicated in the text. is peer reviewed Submitted by Elizabeth Wohlgemuth (wohlgemu@illinois.edu) on 2013-05-29T15:25:20Z No. of bitstreams: 1 Bulletin25(3).pdf: 8625312 bytes, checksum: 288231bc8666ad57fa63e2a8560551ec (MD5) Made available in DSpace on 2013-05-29T15:25:20Z (GMT). No. of bitstreams: 1 Bulletin25(3).pdf: 8625312 bytes, checksum: 288231bc8666ad57fa63e2a8560551ec (MD5) Previous issue date: 1950-03 published or submitted for publication